Artificial Acellular Feeder Layer: An Advanced Engineered Extracellular Matrix for Stem Cell Culture - Haque, Amranul; Nagaoka, Masato; Yue, Xiao-Shan; Duncan, Stephen A.; Akaike, Toshihiro (IntechOpen, 2011)
None